LEGAL PROTECTION OF WIVES VICTIMS OF DOMESTIC VIOLENCE PERSPECTIVE OF MAQOSYD SYARIAH - Asliani, Asliani; Nurhilmiyah, Nurhilmiyah (Proceeding International Seminar of Islamic Studies, 2024)
Legal protection of wives and children in the household is very important both physically and psychologically. This domestic violence often occurs even the most dominant trigger for the collapse of household mahligai is violence experienced by wives and even children including victims. The most important issue to be discussed in this study is how the forms of legal protection for wives and children victims of psychological violence in the perspective of maqasid al-sharia. The method used in this research is with a normative juridical approach, namely by conducting research based on books of jurisprudence, legal / reference materials by examining theories and concepts of statutory materials related to this research. To process and analyze data obtained from library materials, descriptive-analytical analysis techniques are used. This analysis technique gives an idea of the logical flow of data analysis. As a result of the study revealed that the forms of protection for wives' and children victims of psychological violence in the household are protection of the provision of mental birth, protection of the fulfillment of their rights in the form of good treatment and the right to obtain useful knowledge. In addition, protection against physical, psychic, and sexual violence. In the view of maqasid al-Shari'ah, the form of protection for the wife is categorized as the maintenance of reason, soul and offspring as a manifestation of al-maqasid al-Shari'ah at the level of dharuriya.